1980
DOI: 10.1021/bi00547a019
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K dependent carboxylase: subcellular location of the carboxylase and enzymes involved in Vitamin K metabolism in rat liver

Abstract: Vitamin K dependent carboxylation of an exogenous peptide substrate and endogenous protein substrates, vitamin K epoxidation, and reduction of vitamin K epoxide were measured in subcellular fractions from rat liver. The rough microsomal fraction was highly enriched in all four activities; lower levels were found in smooth microsomes. Mitochondria, nuclei, and cytosol had negligible activities. The addition of 0.2% Triton X-100 to intact microsomes resulted in a 10-20-fold stimulation in carboxylation of a pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 36 publications
5
46
0
Order By: Relevance
“…Initial speculation based on protein sequence data and hydrophobicity analysis was that the hydrophilic region in the carboxyl terminus of the enzyme would contain the carboxylase active site. Early studies using selective solubilization of rat liver microsomes (34) showed that the carboxylase activity is facing the lumen of the endoplasmic reticulum. The cDNA sequence of the carboxylase predicts that the C-terminal half of the enzyme is exposed to the lumen because this region has 7 putative Nlinked glycosylation sites.…”
Section: Discussionmentioning
confidence: 99%
“…Initial speculation based on protein sequence data and hydrophobicity analysis was that the hydrophilic region in the carboxyl terminus of the enzyme would contain the carboxylase active site. Early studies using selective solubilization of rat liver microsomes (34) showed that the carboxylase activity is facing the lumen of the endoplasmic reticulum. The cDNA sequence of the carboxylase predicts that the C-terminal half of the enzyme is exposed to the lumen because this region has 7 putative Nlinked glycosylation sites.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, lysine 218, and cysteines 99 and 450 are predicted to be in the lumen of the endoplasmic reticulum where catalytic activity is expected to reside (48). Since very little is known about the tertiary structure of the carboxylase, the proximity of these regions to the region focused in our study is unknown.…”
Section: Vitamin K-dependent Carboxylase Glutamate Binding Residuesmentioning
confidence: 96%
“…Finally, two ion fragments predicted from peptide 92-100 were observed at m/z 662.3 and 889. 4. (Fig.…”
Section: Peptide Mass Fingerprint Of Human Vitamin K-dependentmentioning
confidence: 99%
“…The carboxylation reaction occurs in the lumen of the ER (3,4) and uses the substrates carbon dioxide, oxygen, and vitamin K hydroquinone. During the process of carboxylation, the ␥-proton of the glutamic acid is abstracted, followed by the addition of carbon dioxide (5).…”
mentioning
confidence: 99%